Impacts of English Reading Attitudes on L2 Achievements - Dayan Domisianus Toar; Barli Bram (Indonesian Journal of EFL and Linguistics, 2022)
Reading is an acquired skill needed for obtaining knowledge. To be successful in reading, one should adopt certain attitudes to ensure the reading activity's fruitfulness. This correlational study investigates the possible significant relationship between reading attitude and L2 achievement. The subjects of this study were 47 vocational school students in Yogyakarta. Samples were chosen using purposive sampling with X graders and XI graders of a vocational school. The data were collected through a questionnaire, interview sessions, and an English exam. The hypothesis of this research was the more positive the students’ attitude was, the higher were L2 achievements of the students. The writers conducted a Pearson correlation computation to analyze the correlation of the obtained data. The findings showed that the students' reading attitude was positive and the L2 achievements were high, but the reading attitude correlated negatively and weakly to L2 achievements. Other factors affected L2 achievements as well. ESL teachers should be concerned about their students’ reading attitudes